Arquitetura expansível para desenvolvimento de páginas Ajax - Lucas Eustaquio Gomes da Silva (2009)
Asynchronous web pages have gained popularity over the Internet recently. These pages support more flexible content presentation, because they can change their content without having to reload themselves entirely. The paradigm of asynchronous communication is known as AJAX. However, the development of asynchronous web pages is much more complex. To aid this development, several web frameworks with AJAX support have been created, and many of them are available for free download on the Internet. Each one of these frameworks presents a different approach to solve the problem of asynchronous communication. The biggest critic to all of them is that they aredesigned to work only with DHTML/HTML. They do not offer AJAX support to other technologies such as Silverlight and SVG (Scalable Vector Graphics). Exception made only to the non open-source Microsoft .Net framework, which supports Silverlight. The objective of this work is to produce an expandable web framework architecture that supports other technologies besides HTML. Initially, support for SVG and Silverlight was added. By architecture we mean the class modeling with welldefinedroles and responsibilities. Classes used in both server-side application and client-side application are considered. To achieve this objective, the technologies involved in an AJAX request were studied. Implementation problems and server-side architectures were also discussed. The proposed architecture was built upon the pattern MVC (Model View Controller). To demonstrate the feasibility of this architecture, a framework named KIS (Keep It Simple) was implemented in C #.